The treasure behind the haystack: MUSE analysis of five recently discovered globular clusters - Gran, F.; Kordopatis, G.; Zoccali, M.; Hill, V.; Saviane, I.; Navarrete, C.; Rojas-Arriagada, A.; Carballo-Bello, J.; Hartke, J.; Valenti, E.; Ramos, Contreras R.; Leo, M.; et al. (EDP Sciences, 2026)
Context
After the second data release of Gaia, the number of new globular cluster candidates has increased significantly. However, most of them need to be properly characterised, both spectroscopically and photometrically, by means of radial velocities, metallicities, and deeper photometric observations.
Aims
Our goal is to provide an independent confirmation of the cluster nature of Gran 4, a recently discovered globular cluster, with follow-up spectroscopic observations. The derived radial velocity for individual stars, coupled with proper motions, allows us to isolate cluster members from field stars, while the analysis of their spectra allows us to derive metallicities. By including in the analysis the recently confirmed clusters Gran 1, 2, 3, and 5, we aim to completely characterise recently discovered globular clusters.
Methods
Using Gaia DR3 and VVV catalogue data and MUSE at VLT observations, we selected cluster members based on their proper motions, radial velocities and their position in colour-magnitude diagrams. Furthermore, full spectral synthesis was performed on the cluster members, extracting surface parameters and metallicity from MUSE spectra. Finally, a completeness estimation was performed on the total globular cluster population of the Milky Way.
Results
We confirm the nature of Gran 4, a newly discovered globular cluster behind the Galactic bulge, with a mean radial velocity of RV = −265.28 ± 3.92 km s−1 and a mean metallicity of [Fe/H] = −1.72 ± 0.32 dex. Additionally, independent measurements of the metallicities were derived for Gran 1, 2, 3, and 5. We also revise the observational lower mass limit for a globular cluster to survive in the bulge and disc environment. We estimate that ∼ 12 − 26 globular clusters have still to be discovered on the other side of the Galaxy (i.e., behind the bulge/bar/disk), up to 20 kpc.